Atrial cardiopathy and stroke mortality in the general population. Issue 6 (August 2020) - Ahmad, Muhammad I; Singleton, Matthew J; Bhave, Prashant D; Kamel, Hooman; Soliman, Elsayed Z
Background: Prior studies examining the link between atrial cardiopathy and stroke risk have focused mainly on non-fatal stroke. Aims: To examine the association between atrial cardiopathy and stroke mortality. Methods: This analysis included 8028 participants (60.0 ± 13.4 years, 51.9% women, 49.8% white) from the Third National Health and Nutrition Examination (NHANES III) Survey. Atrial cardiopathy was defined as abnormal deep terminal negativity of the P wave in V1 (DTNPV1 = negative p-wave in V1<−100 µv), an electrocardiographic marker of atrial cardiopathy. Stroke mortality was ascertained using the National Death Index over a median follow-up of 14 years. Results: 2.95% ( n  = 237) of the participants had atrial cardiopathy, and the prevalence was slightly higher in blacks (4%) versus whites (3%). During follow-up, stroke mortality was more common in those with (5.9%) than those without (2.7%) atrial cardiopathy; p  = .004. In a multivariable adjusted model, atrial cardiopathy was associated with a 76% increased risk of stroke mortality (HR (95% CI): 1.76 (1.02–3.04)]. This association was stronger in non-whites than whites (HR (95% CI): 3.50 (1.74–7.03) vs. 0.98 (0.40–2.42), respectively; interaction p  = 0.03). Among those with baseline atrial cardiopathy, the annualized stroke mortality rates/1000 participants across CHA2 DS2 -VASc scores of 0, 1, and ≥2 were 0.0, 2.2, and 7.8, respectively. Conclusions: Atrial cardiopathy is associated with an increased risk of stroke mortality, especially among non-whites. Among those with atrial cardiopathy, the risk of stroke mortality exponentially increases as the CHA2 DS2 -VASc score becomes 2 or above. Randomized controlled trials are needed to assess the efficacy of anticoagulation in the prevention of ischemic stroke and thus, stroke mortality in the presence of atrial cardiopathy.